Pitfalls of Participatory Programs : Evidence from a Randomized Evaluation in Education in India - Banerjee, Abhijit V.; Banerji, Rukmini; Duflo, Esther; Glennerster, Rachel; Khemani, Stuti (World Bank, Washington, DC, 2012)
Participation of beneficiaries in the monitoring of public services is increasingly seen as key to improving their efficiency. In India, the current government flagship program on universal primary education organizes community members, specifically locally elected leaders and parents of children enrolled in public schools, into committees and gives these powers over resource allocation, monitoring and management of school performance. However, in a baseline survey this paper finds that people were not aware of the existence of these committees and their potential for improving education. The paper evaluates three different interventions to encourage beneficiaries' participation: providing information, training community members in a new testing tool, and training and organizing volunteers to hold remedial reading camps for illiterate children. The authors find that these interventions had no impact on community involvement in public schools, and no impact on teacher effort or learning outcomes in those schools. However, the intervention that trained volunteers to teach children to read had large impact on activity outside public schools -- local youths volunteered to be trained, and children who attended these camps substantially improved their reading skills. These results suggest that citizens face substantial constraints in participating to improve the public education system, even when they care about education and are willing to do something to improve it.